Ensaios operacionais para a identificaç\~ao de cidades médias - Rosa Moura; Gustavo Ferreira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2021)
– In this text, we report the operational procedures of two trials carried out to identify Brazilian medium-sized cities, and two possibilities of refinement in identification are included in them, one of urban order and the other of rural order. With these reports, the work aims to discuss the need to seek appropriate methodological and operational procedures to capture, under various dimensions, the specificities of the municipalities, before formulating public policies with territorial incidence in a given category of city. The tests carried out consider the universe of 5,570 municipalities in Brazil, and use comparable information, therefore produced on the same methodology, which express the main characteristics of the municipalities and differentiate them from each other in view of the heterogeneity of the set. The information considered and the results of the classifications are part of an annex made available together with the work. The text is structured in four segments. In the first, the conceptual understanding of the term middle city, its functions and the role of these in the network of cities is resumed briefly, as well as in the process of productive restructuring at the end of the 20th century. Starting from this identification to aggregate other elements identifying specificities: insertion in population arrangements; the nature of these population arrangements; and some poles of immediate regions, not captured by the previous criteria, which in areas of low occupancy density exert polarization over large occupied extensions. In the third segment of the study, the search for the specificities of the set identified from two complementary refinements to the classifications is exercised. As final considerations, in the fourth segment, the diversity found among the municipalities that can be considered as medium cities and contemplated in public policies focused on this category of centers in Brazil is emphasized.
Keywords: R; R11; R12; 330; medium cities; Brazilian municipalities; population arrangements; REGIC